1999
DOI: 10.1590/s0100-204x1999000600014
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre dois métodos analíticos para determinação da lignina de algumas gramíneas forrageiras

Abstract: Foram comparados dois métodos analíticos para a determinação da lignina (lignina em detergente ácido - LDA e lignina permanganato de potássio - LPer) bem como para averiguar a possível relação dos teores desse componente com a digestibilidade da fibra dos seguintes fenos: andropogon (Andropogon gayanus); aveia (Avena sativa); e dois tipos de coast-cross (Cynodon dactylon), um bem fenado e outro de baixa qualidade. Os valores de LDA e LPer foram diferentes (p <= 0,05) entre as gramíneas estudadas, com as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
1
0
3
Order By: Relevance
“…When comparing the heights of cutting in each evaluation period there was no significant difference (P<0.05); however, the CP values decreased at the time of baling in the time of cutting, and rose after storage. Similar CP levels were obtained in white oat hay (129.0 g/kg) by Fukushima et al (1999), while Floss et al (2003) observed lower levels (83.5 g/kg) after 87 days of oat growth. Working with black oats, Moreira et al (2005) found higher CP levels (190 and 130 g/kg) with the first cut (64 days of growth) and with regrowth (56 days of growth).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…When comparing the heights of cutting in each evaluation period there was no significant difference (P<0.05); however, the CP values decreased at the time of baling in the time of cutting, and rose after storage. Similar CP levels were obtained in white oat hay (129.0 g/kg) by Fukushima et al (1999), while Floss et al (2003) observed lower levels (83.5 g/kg) after 87 days of oat growth. Working with black oats, Moreira et al (2005) found higher CP levels (190 and 130 g/kg) with the first cut (64 days of growth) and with regrowth (56 days of growth).…”
Section: Resultssupporting
confidence: 66%
“…The values found are above those recommended for ruminants of 550-600 g/kg of feed (Mertens, 1994). Fukushima et al (1999) studied different componentsof the diet of sheep and found lower levels of NDF (570 g/kg) in oat hay, while Floss et al (2003) found an NDF content of 620 g/kg in oats with 103 days of growth. These differences are primarily related to climatic conditions and stages of plant development.…”
Section: Resultsmentioning
confidence: 99%
“…Enquanto a digestibilidade da matéria seca foi similar entre diversos fenos de forrageiras, a mesma situação não se verificou entre as digestibilidades das fibras em detergente neutro e ácido (FUKUSHIMA et al, 1999). Leguminosas caracteristicamente tendem a possuir menor conteúdo de parede celular (altamente lignificado) e maior de conteúdo celular, relativo às gramíneas ( VAN SOEST, 1994).…”
unclassified
“…FUKUSHIMA et al (1999) Figura 32. Médias entre oito cultivares de avei a nos diversos estádios de maturidade, nos quatro métodos analíticos, para a determinação das ligninas, das três frações, expressos em matéria seca (%).…”
Section: Figura 5 Efeito Das Idades Na Densidade óPtica Da Lignina Dunclassified